2020
DOI: 10.2141/jpsa.0190044
|View full text |Cite
|
Sign up to set email alerts
|

<i>Lactobacillus reuteri</i> Enhances the Mucosal Barrier Function against Heat-killed <i>Salmonella</i> Typhimurium in the Intestine of Broiler Chicks

Abstract: Salmonella Typhimurium (ST) infection in chickens inhibits their growth and can lead to food-borne diseases in humans. Probiotics are expected to enhance the function of host intestinal barrier against pathogen infection. The aim of our study was to determine the effect of viable Lactobacillus reuteri (LR) on the response of the mucosal barrier function to antigen stimulation in broiler chicks. Day-old male (n=8) and female (n=4) broiler chicks were orally administered either 1×10 8 LR or a water-only control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In our study, L. reuteri treatment increased the gene expression of JAM2 in the digestive tract of broiler chicks (Nii et al, 2020c). L. reuteri also increased the expressions of Claudin1, Claudin5, JAM2, and ZO2, and decreased cecal permeability in the cecum of Salmonella Typhimurium heat-killed bacteria stimulated broiler chicks (Nii et al, 2020d). In addition, L. reuteri and C. butyricum treatment enhanced the expression of TLRs, AvBDs, and pro-and anti-inflammatory cytokine genes (Terada et al, 2020).…”
Section: Improvement Of Mucosal Immune Function By Probioticssupporting
confidence: 55%
See 1 more Smart Citation
“…In our study, L. reuteri treatment increased the gene expression of JAM2 in the digestive tract of broiler chicks (Nii et al, 2020c). L. reuteri also increased the expressions of Claudin1, Claudin5, JAM2, and ZO2, and decreased cecal permeability in the cecum of Salmonella Typhimurium heat-killed bacteria stimulated broiler chicks (Nii et al, 2020d). In addition, L. reuteri and C. butyricum treatment enhanced the expression of TLRs, AvBDs, and pro-and anti-inflammatory cytokine genes (Terada et al, 2020).…”
Section: Improvement Of Mucosal Immune Function By Probioticssupporting
confidence: 55%
“…Our previous study showed that oral administration of 1 × 10 8 cfu of L. reuteri increased villus height in the ileum of broiler chicks (Nii et al, 2020c;Nii et al, 2020d). Therefore, probiotics are expected to improve intestinal health by increasing the V/C ratio.…”
Section: Improvement Of Mucosal Immune Function By Probioticsmentioning
confidence: 99%
“…Probiotics are beneficial live bacteria that improve host animal health. The function of them has been well studied for its positive effects on intestinal health in poultry ( Awad et al, 2010 ; Nii et al, 2020a ). Lactobacillus and Bifidobaterium are biological barriers in the intestinal mucosal microflora that maintain the mucosal immune system by suppressing adhesion and colonization of pathogenic bacteria ( O'Hara and Shanahan, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, other genera and species are more characteristic for distal parts of the intestinal tract, and this is common among distantly related species such as humans, pigs or chickens ( Figure 1 ). Despite this, Lactobacilli and Bifidobacteria are used in all these species as probiotics [ 26 , 27 , 28 ],. In some cases, even the same species, such as Lactobacillus plantarum , has been tested in different hosts [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%